Management of integrated management of solid waste in the German hospital in Managua Nicaragua - Blandón, K.; Castellanos, Z. (Nexo Revista Científica, 2010)
Key words: hospital solid waste, management DOI: 10.5377/nexo.v23i2.238 Nexo: Revista Científica Vol. 23, No. 02, pp.53-61/Nov 2010